the Factors Affecting the Export Performance of Sporting Products to Achieve a World Class with an Emphasis on Human Resource Development - Forough Mohammadi; Narges Azam nezami; Masoumeh Kalateh; Mohammad Hossein Razavi; Hasan Farsijani (Islamic Azad university, Isfahan Branch, 2022)
The purpose of this paper was to level the factors affecting the export performance of sports products to reach the global class with an emphasis on human resource development by employing interpretive-structural modeling. The current research is a mixture of developmental and applied. Based on the Galyzeri approach and deep interview with 15 people (sports marketing, economists, industrial management) in the NVIVO10 software environment, the main factors of the model were identified in the form of 92 open source, 13 selective and 5 theoretical codes, and then using the interpretive- The structure in the MATLAB2014 software Based on the Galyzeri approach and deep interview with 15 people (sports marketing, economists, industrial management) in the NVIVO10 software environment, the main factors of the model were identified in the form of 92 open source, 13 selective and 5 theoretical codes, and then using the interpretive- The structure in the MATLAB2014 software environment is the level and internal relationships between extraction factors and finally classified based on MICMAC analysis of power and dependency. The results showed that model factors are located in 5 levels and motivate people for human resources, trust building, organizational communication, training and human resource skills at the fifth level of the model and have the most impact on human resource development (level four), quality, Innovation, flexibility, cost reduction, time reduction, sales and after-sales services (third level), production and service in the world class (second level), world-class sports industry, and the empowerment of export performance of sports products (Level one) . In MICMAC analysis, human resource development factors (independent variables) that stimulate and motivate other factors. Based on the results of the research, successful and effective sports managers and marketers, by establishing effective communication mechanisms with individuals inside and outside the organization, identifying and educating people, empowering, motivating, and building trust can lead to the development of world-class human resources to the extent of empowerment The export performance of sports products and the boom in the production of Iranian sports goods are provided.by establishing effective communication mechanisms with individuals inside and outside the organization, identifying and educating people, empowering, motivating, and building trust can lead to the development of world-class human resources to the extent of empowerment The export performance of sports products and the boom in the production of Iranian sports goods are provided.